Numerical simulation of pulsed plasma thruster with a preionization helicon discharge - Kuzenov, V.V.; Polozova, T.N.; Ryzhkov, S.V. (Вопросы атомной науки и техники, 2015)
The major electrical characteristics of pulsed coaxial magneto-plasma accelerator with a capacitive power source are calculated on the basis of approximate mathematical model of pulsed plasma thruster, preionization system of working gas with a helicon discharge and multiparametric optimization of CMPA by methods of computational experiment. The main parameters of the RF source and physical characteristics of argon plasma are presented. Initial assessments are conducted prior to plasma acceleration using helicon preionization source and main characteristics of coaxial magneto-plasma accelerator.